China Contest for Cultural and Multi-Lingual Centres and its Attraction in South Asia - Bukhari, Munazzah (Annals of Human and Social Sciences, 2025)
The study explores China’s Belt and Road Initiative (BRI) as a 21st-century soft power and its approach for cultural diplomacy. This article examines how China influences through media, education, infrastructural development, and cultural interchange program to enhance its power in Asia. The study analyzes China’s employment of cultural diplomacy within the framework of the BRI using a qualitative methodology and secondary sources, such as academic publications, governmental papers, and reports. According to the study, China successfully use cultural diplomacy to foster regional cooperation and steer clear of political disputes. China promotes cultural awareness and understanding among Asian countries through programs like international arts festivals, educational initiatives, and Confucius Institutes. Large-scale infrastructure initiatives under the BRI also increase China’s cultural influence while fostering economic connection. China’s soft power approach is further enhanced by its involvement with regional institutes such as the Asian Infrastructure Investment Bank, the Shanghai Cooperation Organization, and ASEAN. According to the findings, the BRI strengthens China’s position as the region’s leader by acting as a potent cultural diplomacy instrument in addition to being an economic project. Long-term diplomatic and commercial ties are eventually fostered by the growth of cultural exchange programs and the propagation of Confucian ideals, which enhance China’s favorable international reputation.